Faith and fatherland: catholicism, modernity, and Poland - Porter, Brian (Oxford University Press, 2011)
The church -- Sin -- Modernity -- The person and society -- Politics -- The nation penitent -- Ecclesia militans -- The Jew -- Polak-Katolik -- Mary, militant and maternal